Youth living with HIV/AIDS in secondary schools: perspectives of peer educators and patron teachers in Western Uganda on stressors and supports - Emmanuel Kimera; Sofie Vindevogel; John Rubaihayo; Didier Reynaert; Jessica De Maeyer; Anne-Mie Engelen; Johan Bilsen (Taylor & Francis Group, 2019)
As Youth Living With HIV/AIDS (YLWHA) continue to survive and live with HIV chronically due to effective Antiretroviral Therapy (ART), it is paramount to work toward maximising their psychosocial wellbeing. The school where these YLWHA are expected to spend most of their time is an excellent environment to investigate this. In this study, we explore perspectives of Peer Educators (PEs) in secondary schools of one district in Western Uganda on how YLWHA are perceived in school, on their daily stressors and their way of coping with their HIV-positive serostatus given the support of the schools. We conducted eight focus groups with a total of 59 students who were members of Peer Educators Clubs (PECs) as well as 8 in-depth interviews with patron teachers of PECs in eight secondary schools of Kabarole district, selected through a stratified random sampling method. Focus groups and interviews were tape-recorded, transcribed and analysed thematically both inductively and deductively. Stressors and support in schools, as identified by the PEs were categorised into three interrelated thematic domains; psychological wellbeing of YLWHA, disclosure of HIV status by YLWHA, and health and treatment adherence. Stigma was found to be a key stressor and an intermediary in all the three thematic domains Stressors affecting psychological wellbeing were fear of death and uncertainty of the future compounded by financial and academic challenges. Stressors affecting disclosure centred around lack of privacy, confidentiality and fear of loss of friends. Stressors affecting treatment adherence included lack of privacy while taking drugs, unintended disclosure while obtaining drugs or seeking permission to attend clinic appointments and fear of drug adverse effects due to poor nutrition. A supportive school environment involved the availability of a school nurse, counselling services and PECs. We conclude that the school environment brings more stressors than supports for YLWHA. The daily stressors related to HIV stigma, uncertainty, disclosure, privacy and confidentiality render schooling a hassle for YLWHA. Interventions that promote resilient school communities are necessary to foster disclosure in a non-discriminatory and stigma-free environment. This calls for concerted efforts from all school stakeholders.